Thread: Exercise 3.4(a)
View Single Post
  #1  
Old 10-08-2014, 06:33 PM
squidsforlunch squidsforlunch is offline
Junior Member
 
Join Date: Oct 2014
Posts: 1
Default Exercise 3.4(a)

For Exercise 3.4 (a) I did

y = w*^{T}X+E
\hat{y} = Hy
\hat{y} = H(w*^{T}X+E)
\hat{y} = Hw*^{T}x+HE
\hat{y} = (X(X^{T}X)^{-1}X^{T})w*^{T}X+HE
\hat{y} = (XX^{-1}(X^{T})^{-1}X^{T})w*^{T}X+HE
\hat{y} = (I(X^{T})^{-1}X^{T})w*^{T}X+HE
\hat{y} = (I(I))w*^{T}X+HE
\hat{y} = w*^{T}X+HE

but
w*^{T}X
is not equal to
Xw*
What am I missing?
Reply With Quote